Renal Endothelial Cell‐Targeted Extracellular Vesicles Protect the Kidney from Ischemic Injury (Adv. Sci. 3/2023). Issue 3 (25th January 2023) - Zhang, Kaiyue; Li, Rongrong; Chen, Xiaoniao; Yan, Hongyu; Li, Huifang; Zhao, Xiaotong; Huang, Haoyan; Chen, Shang; Liu, Yue; Wang, Kai; Han, Zhibo; Han, Zhong‐Chao; et al.
Abstract : Acute Kidney Injury Endothelial cell injury is one of the specific features of acute kidney injury (AKI). In article number 2204626, Zongjin Li and co‐workers identify P‐selectin as a biomarker of ischemic AKI in endothelial cells and develop P‐selectin binding peptide‐engineered extracellular vesicles (PBP‐EVs) with imaging and therapeutic functions targeting injured endothelial cells for the first time.